Cell Technologies in the Treatment of Chronic Wounds in Patients with Diabetes Mellitus - Ivanova, Yu. V.; Gramatiuk , S. M.; Prasol, V. O.; Miasoiedov, K. V.; Zarudnyi, O. O.; Holtsev, K. A. (Transplantation and artificial organs, 2021)
Materials and methods. The results of treatment of 8 patients with chronic wounds and diabetes mellitus (DM) type 2 and stage IV chronic ischemia of the lower extremities by Fontaine were analyzed, in 2 cases there was a combination of venous and arterial insufficiency. Revascularization of the lower extremities was performed through open (2), endovascular (4) and hybrid surgery (2). In case of venous insufficiency, sclerotherapy of perforator veins was performed. After surgical treatment of the purulent focus, specific bacteriophages were used (after microflora identification). Hydrogel dressings were applied daily, alongside with transplantation of 5,000,000 mesenchymal stem cells (MSC) (CD73+, CD90+, CD105+ and CD45-, CD34-, CD14-, CD79-) by injection into muscle tissue around the wound, then the wound surface was closed with hMSC-fibroblast matrix. Results. After the closure of the wound surface with fibroblast matrix, the patients noted the disappearance of the pain syndrome. The surface area of the wounds averaged 91.3 ± 30.42 cm 2 before the start of treatment, 89.8 ± 34.21 cm 2 on day 5 and – 73.95 ± 21.2 cm 2 on day 12. Spontaneous epithelialization was achieved in the period from 35 to 141 days (depending on the initial state of the wounds). The average hospital stay was 22.6 ± 2.4 days. Discussion. It is known that human epithelial cells (hECs) and human mesenchymal stem cells (hMSCs) suppress proliferation, production of inflammatory cytokines and differentiation of T cells. At the same time, they stimulate the formation of regulatory T cells (Tregs). Soluble factors secreted by hECs, including PGE2, TGF-β, Fas-L, AFP, MIF, TRAIL and HLA-G, block differentiation of dendritic cells and M1 macrophages and promote differentiation of monocytes into the anti-inflammatory M2 phenotype. Moreover, hECs and hMSCs are known to be responsible for modulating the host immune system, mainly by suppressing TNF-α, IFN-γ, MCP-1 and IL-6 and increasing the level of anti-inflammatory cytokines. In vitro and in vivo results show increased cell migration and epithelialization leading to accelerated wound healing.